Cardiovascular Effects of Unilateral Nephrectomy in Living Kidney Donors. Issue 2 (February 2016) - Moody, William E.; Ferro, Charles J.; Edwards, Nicola C.; Chue, Colin D.; Lin, Erica Lai Sze; Taylor, Robin J.; Cockwell, Paul; Steeds, Richard P.; Townend, Jonathan N.
Abstract : Abstract—: There is a robust inverse graded association between glomerular filtration rate (GFR) and cardiovascular risk, but proof of causality is lacking. Emerging data suggest living kidney donation may be associated with increased cardiovascular mortality although the mechanisms are unclear. We hypothesized that the reduction in GFR in living kidney donors is associated with increased left ventricular mass, impaired left ventricular function, and increased aortic stiffness. This was a multicenter, parallel group, blinded end point study of living kidney donors and healthy controls (n=124), conducted from March 2011 to August 2014. The primary outcome was a change in left ventricular mass assessed by magnetic resonance imaging (baseline to 12 months). At 12 months, the decrease in isotopic GFR in donors was −30±12 mL/min/1.73m 2 . In donors compared with controls, there were significant increases in left ventricular mass (+7±10 versus −3±8 g; P <0.001) and mass:volume ratio (+0.06±0.12 versus −0.01±0.09 g/mL; P <0.01), whereas aortic distensibility (−0.29±1.38 versus +0.28±0.79×10 −3 mm Hg −1 ; P =0.03) and global circumferential strain decreased (−1.1±3.8 versus +0.4±2.4%; P =0.04). Donors had greater risks of developing detectable highly sensitive troponin T (odds ratio, 16.2 [95% confidence interval, 2.6–100.1]; P <0.01) and microalbuminuria (odds ratio, 3.8 [95% confidence interval, 1.1–12.8]; P =0.04). Serum uric acid, parathyroid hormone, fibroblast growth factor-23, and high-sensitivity C-reactive protein all increased significantly. There were no changes in ambulatory blood pressure. Change in GFR was independently associated with change in left ventricular mass ( R 2 =0.28; P =0.01). These findings suggest that reduced GFR should be regarded as an independent causative cardiovascular risk factor. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01028703. Abstract : Supplemental Digital Content is available in the text.